Republic of Tajikistan : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Tajikistan is not a HIPC country. It is, however, eligible under the MDRI because it had a per capita annual GDP of below USD 380 as of 2004. Staff is of the view that all criteria have been met, and recommends that the Board determine that Tajikistan qualifies for immediate debt relief under the MDRI.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet